Effects of arousal and valence on center of pressure and ankle muscle activity during quiet standing. - Ryogo Takahashi; Naotsugu Kaneko; Hikaru Yokoyama; Atsushi Sasaki; Kimitaka Nakazawa (PLoS ONE, 2024)
Emotion affects postural control during quiet standing. Emotional states can be defined as two-dimensional models comprising valence (pleasant/unpleasant) and arousal (aroused/calm). Most previous studies have investigated the effects of valence on postural control without considering arousal. In addition, studies have focused on the center of pressure (COP) trajectory to examine emotional effects on the quiet standing control; however, the relationship between neuromuscular mechanisms and the emotionally affected quiet standing control is largely unknown. This study aimed to investigate the effects of arousal and valence on the COP trajectory and ankle muscle activity during quiet standing. Twenty-two participants were instructed to stand on a force platform and look at affective pictures for 72 seconds. The tasks were repeated six times, according to the picture conditions composed of arousal (High and Low) and valence (Pleasant, Neutral, and Unpleasant). During the task, the COP, electromyogram (EMG) of the tibialis anterior and soleus muscles, and electrocardiogram (ECG) were recorded. The heart rate calculated from the ECG was significantly affected by valence; the value was lower in Unpleasant than that in Neutral and Pleasant. The 95% confidence ellipse area and standard deviation of COP in the anterior-posterior direction were lower, and the mean power frequency of COP in the anterior-posterior direction was higher in Unpleasant than in Pleasant. Although the mean velocity of the COP in the medio-lateral direction was significantly lower in Unpleasant than in Pleasant, the effect was observed only when arousal was low. Although the EMG variables were not significantly affected by emotional conditions, some EMG variables were significantly correlated with the COP variables that were affected by emotional conditions. Therefore, ankle muscle activity may be partially associated with postural changes triggered by emotional intervention. In conclusion, both valence and arousal affect the COP variables, and ankle muscle activity may be partially associated with these COP changes.